In search of Gandhi : essays and reflections - Nanda, B. R. (Bal Ram), 1917-2010. (Delhi ; Oxford : Oxford University Press, 2004)
This is a collection of 29 essays by a noted scholar of Ghandian studies. Together, they present a composite picture of Gandhi's life and thought.
Originally published: 2002.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Gandhi, -- Mahatma, -- 1869-1948.; Statesmen -- India -- Biography; Pacifists -- India -- Biography